Estudio Geológico Estructural y Determinación de la Calidad del Macizo Rocoso de la Galería de Exploración T1 en el Área Minera Cambanas (Código 246) Ubicado en la Parroquia San Carlos de las Minas, Cantón Zamora, Provincia de Zamora Chinchipe - Uchuari Quezada, Harman Mauricio (2020)
The present investigation refers to the "Geological structural study and determination of the quality of the rock mass of the T1 exploration gallery in the Cambanas mining area (code 246) located in the San Carlos de las Minas Parish, Zamora County, Zamora Chinchipe Province", covering an area of 19.59 contiguous mining hectares. Once the surface and underground topography and surface geology were obtained, this information was corroborated and the geology was determined by taking samples. These samples were found in the Nambija Mining District in a skarn-type deposit, composed of andesite rocks, metamorphic rocks resulting from contact metamorphism and an andesite composition dyke. In the geological structural survey of the gallery several main drag faults were determined with a NW direction with dips between 30° and 75° SW and the lithological contacts present a NE direction with dips between 73° and 86° SE. An evaluation of the physical properties was made: density and specific weight and the mechanical properties: rebound resistance of the Schmidt hammer, simple compression and tensile strength. For the geomechanical characterization RMR (Bieniawski 1989) four sectors were considered according to the identification of their geological features and structural domains determining that the quality of the rock mass is type II (Good) and type III (Regular). Barton's geomechanical Q characterization was carried out in the same sectors through direct observation, determining that the quality of the rock mass is Good, Regular and Poor. Whose characterization determined that the geomechanical behavior in the study area is stable or partially stable. Two geomechanical classification systems were used for the correlation, Barton's RMR and Q by means of a logarithmic type relationship; RMR = 7.66 * lnQ + 46.83 is a locally adjusted equation for the results used in the sector and can be used in future work in the mining area, especially in the design and construction of future mining works. Keywords: Structural geology; RMR classification; Q classification; rock mass.